The Potential of Herbal Plants in the Prevention and Treatment of Fish Diseases: A Review - Andriani, Yuli; Aisyah, Aisyah (Journal of Fish Health, 2025)
The use of herbal plants in aquaculture has emerged as a sustainable and eco-friendly approach to improving fish health, enhancing immunity, and boosting growth performance. Various herbs are rich in bioactive compounds that stimulate non-specific defense mechanisms, enhance phagocytic activity, and reduce oxidative stress through their antioxidant properties. These immunostimulatory effects improve disease resistance and overall well-being in fish. Additionally, herbal supplementation has demonstrated significant growth-promoting effects by improving feed conversion efficiency and productivity in aquaculture systems. This review summarizes the roles of key herbal plants in aquaculture, highlighting their potential as natural alternatives to synthetic chemicals and antibiotics. The findings underscore the importance of integrating herbal remedies into aquaculture practices to enhance fish health and sustainability.